Pendampingan Sistem Informasi Akuntansi Pengadaan Barang Pada PT Jetcoms Netindo - Iis Wahyuni; Marwan Effendy; Githa Ariyanty (LPPM Institut Bisnis dan Informatika Kesatuan, 2021)
Procurement of goods (purchase) is the main thing in carrying out the company's operational activities. Due to the complexity of purchasing procedures, companies should have interrelated functions to realize good and well-controlled purchasing activities. Purchasing accounting information systems are needed to avoid errors and fraud that can occur in carrying out purchasing activities. In the procurement accounting information system (purchase) it must have advantages and disadvantages, therefore it is necessary to have a review and evaluation as a reference for improvement so that it becomes a good and perfect purchasing accounting information system. This study aims to find out how the procedures for procurement activities (purchases) which include the documents used, related functions, and accounting records used in the procurement accounting information system applied to PT Jetcoms Netindo. In my opinion, the procurement (purchase) procedure at PT Jetcoms Netindo is good enough, but still has some weaknesses. The weaknesses include the existence of tasks and responsibilities that are too piled up in one section, and the lack of accounting records used. It would be better if the separation of functional duties could be more clearly separated. Keywords: purchase, purchasing accounting information system